Formação continuada de professores do ensino básico, técnico e tecnológico: investigação do itinerário formativo - Oliveira, Elza Galdino de (2019)
The Federal Centers of Technological Education (CEFETs), when transformed into Federal Institutes of Education, Science and Technology (IFs), with Law nº 11.892 / 2008, started to offer teaching at all levels and modalities, including degrees and pedagogical training of professors, in addition to lato and stricto sensu graduate courses. In this context, we are interested in looking at the trajectory of continuing education for teachers who start to work in the federal system and invest in their training as teachers of Technological Professional Education (EPT). Our main objective was to investigate the formative itinerary of teachers of Basic, Technical and Technological Education (EBTT) of the Federal Institute of Education, Science and Technology of Paraíba (IFPB) and the teaching knowledge prioritized by them. For this, we base our research on studies about the process of continuing teacher education for higher education, defended by Imbernón (2009, 2011), Tardif (2002), Pimenta (1999), Freire (1996), among other researchers. This work consisted of a case study, which followed the qualitative and exploratory research process, using the Federal Institute of Education, Science and Technology of Paraíba, Campus João Pessoa as a research field, with a population of sixty-six effective teachers, from two higher education courses, in person, from this institution. The sample consisted of thirty-four permanent professors, twenty-two from the Bachelor of Business Administration course and twelve from the Chemistry Degree. As for the research procedure, we performed document analysis, analysis of the Lattes curriculum and applied a semi-structured questionnaire. The data generated were treated through content analysis (BARDIN, 2009; FRANCO, 2007). Among the results pointed out in the analyzes, we highlight the investments that teachers made in their training itineraries, with some investing in continued training that contemplated the didactic-pedagogical dimension (SAVIANI, 2009). With the discussions undertaken, we pointed out elements in order to contribute to the consolidation of a policy of continuing education that includes the knowledge necessary to exercise the teaching activity and to face the educational challenges that an institution of professional and technological education implies, considering the specificity of the students. EBTT teachers, with their professional trajectories, profiles and their own training needs.